Management of Educational Facilities and Infrastructure in Improving the Learning Process - Rahayu, Mulyani; Fitria, Happy; Rohana, Rohana (Journal of Social Work and Science Education, 2024)
This study aims to see how SD IT Ishlahul Ummah Prabumulih implements educational facility and infrastructure management to enhance the learning process. The data collection methods used were evaluation, reporting, and interviews, and the approach used was phenomenological descriptive. The principal, deputy principal, person in charge of facilities and infrastructure, treasurer, teachers, and committee chairpersons were all sources of information. Techniques for data analysis include data reduction, data interpretation, and conclusions. Techniques for data analysis include data reduction, data interpretation, and conclusions. The study’s findings revealed that the use of facilities and resources in the learning process was not optimal, especially for educators. The full support of all school members, particularly foundations, is a supporting factor in the facility and infrastructure management process, while the inhibiting factor is a lack of knowledge of the importance of maintaining facilities and infrastructure among educators and students.